Mortality in pulmonary arterial hypertension: prediction by the 2015 European pulmonary hypertension guidelines risk stratification model. Issue 2 (3rd August 2017) - Hoeper, Marius M.; Kramer, Tilmann; Pan, Zixuan; Eichstaedt, Christina A.; Spiesshoefer, Jens; Benjamin, Nicola; Olsson, Karen M.; Meyer, Katrin; Vizza, Carmine Dario; Vonk-Noordegraaf, Anton; Distler, Oliver; Opitz, Christian; et al.
The 2015 European pulmonary hypertension (PH) guidelines propose a risk stratification strategy for patients with pulmonary arterial hypertension (PAH). Low-, intermediate- and high-risk strata are defined by estimated 1-year mortality risks of <5%, 5–10% and >10%, respectively. This risk assessment strategy awaits validation. We analysed data from patients with newly diagnosed PAH enrolled into COMPERA (Comparative, Prospective Registry of Newly Initiated Therapies for Pulmonary Hypertension), a European-based PH registry. An abbreviated version of the risk assessment strategy proposed by the European PH guidelines was applied, using the following variables: World Health Organization functional class, 6-min walking distance, brain natriuretic peptide or its N-terminal fragment, right atrial pressure, cardiac index and mixed venous oxygen saturation. Data from 1588 patients were analysed. Mortality rates were significantly different between the three risk strata (p<0.001 for all comparisons). In the entire patient population, the observed mortality rates 1 year after diagnosis were 2.8% in the low-risk cohort (n=196), 9.9% in the intermediate-risk cohort (n=1116) and 21.2% in the high-risk cohort (n=276). In addition, the risk assessment strategy proved valid at follow-up and in major PAH subgroups. An abbreviated version of the risk assessment strategy proposed by the current European PH guidelines provides accurate mortality estimates in patients with PAH. The risk stratification strategy proposed by the current European PH guidelines allows accurate survival prediction http://ow.ly/KsWk30c46nK